Design, Integration, and Experiment of Transplanting Robot for Early Plug Tray Seedling in a Plant Factory - Wei Liu; Minya Xu; Huanyu Jiang (AgriEngineering, 2024)
In the context of plant factories relying on artificial light sources, energy consumption stands out as a significant cost factor. Implementing early seedling removal and replacement operations has the potential to enhance the yield per unit area and the per-energy consumption. Nevertheless, conventional transplanting machines are limited to handling older seedlings with well-established roots. This study addresses these constraints by introducing a transplanting workstation based on the UR5 industrial robot tailored to early plug tray seedlings in plant factories. A diagonal oblique insertion end effector was employed, ensuring stable grasping even in loose substrate conditions. Robotic vision technology was utilized for the recognition of nongerminating holes and inferior seedlings. The integrated robotic system seamlessly managed the entire process of removing and replanting the plug tray seedlings. The experimental findings revealed that the diagonal oblique-insertion end effector achieved a cleaning rate exceeding 65% for substrates with a moisture content exceeding 70%. Moreover, the threshold-segmentation-based method for identifying empty holes and inferior seedlings demonstrated a recognition accuracy surpassing 97.68%. The success rate for removal and replanting in transplanting process reached an impressive 95%. This transplanting robot system serves as a reference for the transplantation of early seedlings with loose substrate in plant factories, holding significant implications for improving yield in plant factory settings.